Necessity of a new development policy - Sartaj Aziz (Intereconomics, 1972)
In the past two decades, several attempts have been made in the developed countries to outline and pursue a “new policy” for the less developed countries (LDCs). Today, the vision of this concept is no longer as vivid or hopeful as it seemed at the beginning. The meagre results achieved at the third UNCTAD have lent further weight to pessimistic predictions about the future of international cooperation as a major element in world affairs.
Keywords: 330; Trade And Development